A Pilot Study to Promote Active Living among Physically Inactive Korean American Women. Issue 1 (2nd January 2021) - Choi, JiWon; Shin, Nah-Mee; Cooper, Bruce; Jih, Jane; Janice, Tsoh
ABSTRACT: A 4-week lifestyle program called Women's Active Living for Koreans (WALK) was designed for Korean American women to promote physical activity (PA). In a pilot-controlled trial, 40 women were randomized to WALK-regular or WALK-plus. WALK-plus involved joining an online community via a social media app. WALK-plus performed significantly higher numbers of days of muscle-strengthening activities than WALK-regular at the post-intervention visit. Both groups increased vigorous activities and walking and decreased sedentary behaviors on weekdays. WALK program showed great potential in improving PA and decreasing sedentary behaviors. Online social networking may have an additional effect on PA among this population.